Resíduos de mercúrio em peixes comerciais consumidos na Pan-Amazônia - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2022)
Given the high demand for fish consumption by the Amazon population, associated with the problem of contamination of water resources and aquatic biota by metals, there is a need to assess the levels of mercury in foods consumed locally such as fish. And studies that bring together past works for assessments of the mercury contamination scenario are relevant in the direction of contributing to the monitoring of regional food security. Therefore, this research aims to evaluate the levels of mercury concentration in the most consumed commercial fish in the Pan-Amazon, as well as to establish an acceptable daily intake index for mercury residues, based on secondary data. Thus, this research is a systematic bibliographic review from the collection of data and information in different scientific electronic databases for the period from 1997 to 2021, carried out through descriptors related to mercury residues in commercial fish consumed in the Pan-Amazon. It is concluded that mercury concentration levels have increased over the years in carnivorous fish and that carnivorous species are above the threshold of the food safety zone recommended by the World Health Organization. The average concentrations found for carnivorous species was 0.616 µg/g-1, for omnivores 0.299 µg/g-1 and Zooplanktophages 0.411 µg/g-1, herbivore 0.120 µg/g-1 and detritivore 0.096 µg/g-1 . This represents an increase of 641.7% in relation to the trophic level (detritivore and carnivore), showing the great potential for bioaccumulation in the top-of-chain species and the biomagnification that occurs between one link and another. Among the trophic levels, only detritivores and herbivores did not present concentrations above 0.5 μg/g–1, demonstrating that they are the safest groups in relation to mercury concentrations, and these species are considered safe options for human consumption. However, it is important to pay attention to the risk of the frequency that this food is ingested, since mercury is an element with high accumulation power and that, even in low concentrations, its frequent consumption can be harmful to health. Furthermore, the Risk Quotient showed that the consumption of carnivorous and omnivorous species presents great health risks. This brings the possibility of adverse effects, where a high exposure to Hg, even if occasional, can significantly contribute to the increased risk of neurological pathologies in individuals who are being chronically exposed to this element.
Keywords: Mercúrio; Peixes comerciais; Pan-Amazônia; CNPQ::CIÊNCIAS DA SAÚDE::FARMÁCIA::TECNOLOGIA FARMACÊUTICA; Fisiologia Ambiental